FAKTOR-FAKTOR YANG MEMPENGARUHI KECENDERUNGAN KECURANGAN AKUNTANSI DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING - Aisyatul Fitri (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Riau, 2020)
The purpose of this study was to analyze the influence of the Government Internal Control System, Compliance with Accounting Rules, Law Enforcement and Unethical Behavior on the Tendency of Accounting Fraud with Organizational Commitment as an Intervening Variable in Bengkalis Regency. The population in this study was OPD in the Riau Provincial Government. The sample in this study were officials or employees involved in financial management / accounting at OPDs in Bengkalis Regency, amounting to 35 OPDs with 105 respondents. The sampling method is saturated sampling method or census. The data collection method is a survey method. Data analysis using SEM using SMART PLS. The results showed that the government's internal control system, regulatory compliance, law enforcement and unethical behavior had an effect on the tendency of accounting fraud. Organizational commitment is an intervening variable between the government's internal control system, compliance with accounting rules and adherence to accounting rules and the tendency of accounting fraud, but organizational commitment is not an intervening variable between unethical behavior and the tendency of accounting fraud.